Analyzing Fiscal Space Using the MAMS Model : An Application to Burkina Faso. (IMF Working Papers; Working Paper ;, 2009)
This paper analyses economic implications and the transmission mechanisms of different options for creating and using fiscal space. For creating fiscal space, we consider prioritizing expenditures, raising revenue, and scaled-up aid. Fiscal space is used for increasing health and education spending, infrastructure spending, or both. The analysis takes place within the World Bank's MAMS model, which is a multisectoral real computable general equilibrium model that incorporates the Millennium Development Goals. The model has been calibrated for Burkina Faso, which serves as an illustrative country example. Some of the key results are that absorbing a more educated labor force requires fundamental structural change in the economy; increasing health and education spending can face sizeable capacity constraints; and infrastructure spending has a positive effect on growth as well as education and health outcomes.